Repetition, Parody or Disintegration of the Empty Plate of Magic Performatives in Croatian Contemporary Poetry - Pinter, Kornelija; Sorel, Sanjin (Poznańskie Studia Slawistyczne, 2013)
In the article, from different linguistic and literary theoretical perspectives, parodic function of anaphora is analyzed on samples of Croatian contemporary poetry. The aim is to present how a poem, especially one that is not from the contemporary lyric collection, is not a realization of „mythic time”, but in its rhythms and structures, where repetition is condition sine qua non of lyricism, it keeps a trace, a memory of the imaginary, of the myth which in speech revives what is hidden and suppressed.